In recognition of the excellent service and contributions rendered, this university confers upon John G. Daniel the Honorary Degree of Doctor of Civil Engineering - Universiti Teknologi Malaysia 495834; Daniel, John G., addressee 413085; Sultanah Zanariah Almarhum Tunku Ahmad, signer 655367; Ahmad Zaharudin Idrus, Tan Sri, Datuk, Dr., 1944-, signer 386116; Ismail Ibrahim, signer 324675 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 1998)
Universiti Teknologi Malaysia;